The Influence Of Income Level, Tax Knowledge, And Tax Penalty On Taxpayer Compliance In Paying Land And Building Taxes In The Telaga Asih Village Area, West Cikarang, West Java - Rahmatullah; Suryati, Adelina; Arigawati, Desy (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2024)
This study aims to identify the factors influencing taxpayer compliance in paying land and building tax in the Telaga Asih Village, Cikarang Barat Subdistrict, West Java. Therefore, the purpose of this research is to evaluate and analyze the factors affecting tax compliance in the Telaga Asih Village area, West Cikarang Subdistrict, West Java. The study employs a multiple linear regression model using SPSS software version 23. Data were collected through the distribution of questionnaires to taxpayers who are obligated to pay land and building tax in the Telaga Asih Village area of Cikarang Barat Subdistrict, West Java. The sampling technique was conducted using random sampling, resulting in 60 respondents who are taxpayers in the Telaga Asih Village area with a duty to pay land and building tax. The results indicate that income level, tax knowledge, and tax penalties have a significant impact on taxpayer compliance in paying land and building tax.